2022
DOI: 10.4103/ijo.ijo_3207_21
|View full text |Cite
|
Sign up to set email alerts
|

Crouzon syndrome and the eye: An overview

Abstract: The current literature review aims to evaluate the ocular findings and associated ophthalmic features in Crouzon syndrome. Craniosynostoses are syndromes characterized by premature fusion of sutures of the skull and Crouzon syndrome is the most common of the craniosynostosis syndromes. Early fusion of sutures results in craniofacial anomalies, including abnormalities of the orbits. To prepare this review of the ophthalmic findings in this disorder, an organized search on online databases such as PubMed, Scopus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…Of note, the cohort in this study ranged from infanthood to adulthood, allowing comprehensive and chronological development. Our study suggested that maxillary retrusion rapidly aggravated during the 3 to 6 years old, which corroborates with what Lu et al found, confirming that therapeutic interventions, including surgical advancement 22 or nonsurgical orthodontic maxillary expansion 23,24 should be initiated to slow pathologic deterioration. The delay of mandibular rapid aggravation indicates mandibular counterclockwise rotation might be triggered by maxillary retrusion and the covariation of maxillary and mandibular morphological variation should be further investigated to determine whether intervention should be enforced on the mandible independently or not.…”
Section: Discussionsupporting
confidence: 91%
“…Of note, the cohort in this study ranged from infanthood to adulthood, allowing comprehensive and chronological development. Our study suggested that maxillary retrusion rapidly aggravated during the 3 to 6 years old, which corroborates with what Lu et al found, confirming that therapeutic interventions, including surgical advancement 22 or nonsurgical orthodontic maxillary expansion 23,24 should be initiated to slow pathologic deterioration. The delay of mandibular rapid aggravation indicates mandibular counterclockwise rotation might be triggered by maxillary retrusion and the covariation of maxillary and mandibular morphological variation should be further investigated to determine whether intervention should be enforced on the mandible independently or not.…”
Section: Discussionsupporting
confidence: 91%
“…A new technique, craniofacial disjunction, followed by gradual bone distraction (Ilizarov procedure) can be carried out to correct exophthalmos and improve the functional and esthetic aspects of the middle third of the face without requirement for bone graft in patients aged 6-11 years. [5,6]…”
Section: Discussionmentioning
confidence: 99%
“…Proper treatment plan by multidisciplinary approach utilizing modern methods will achieve good outcome and improve quality of patient's life. [5,6]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical management typically involves several phases targeting specific structures. The first phase usually involves remodeling the fronto-orbital area and releasing stenotic sutures so that proper brain growth can occur [ 7 , 11 ]. Once the child reaches late adolescence, corrections including midfacial, orthodontic, and orthognathic surgery are performed to ensure a more normal cosmetic appearance [ 7 , 11 ].…”
Section: Discussionmentioning
confidence: 99%